White dwarf stars: cosmic chronometers and dark matter probes. (7th March 2018) - Salaris, Maurizio; Cassisi, Santi
Abstract: White dwarfs (WD) are the endpoint of the evolution of the large majority of stars formed in our galaxy. In the last two decades observations and theory have improved to a level that makes it possible to employ WD for determining ages of the stellar populations in the disk of the Milky Way and in the nearest star clusters, and constrain the existence and properties of dark matter (DM) candidates. This review is centred on WD models, age-dating, and DM identification methods, recent results and future developments of the field.